Crosstalk between Tryptophan Metabolism and Cardiovascular Disease, Mechanisms, and Therapeutic Implications. (9th March 2017) - Liu, Gang; Chen, Shuai; Zhong, Jin; Teng, Kunling; Yin, Yulong
Abstract : The cardiovascular diseases (CVD) associated with the highest rates of morbidity are coronary heart disease and stroke, and the primary etiological factor leading to these conditions is atherosclerosis. This long-lasting inflammatory disease, characterized by how it affects the artery wall, results from maladaptive immune responses linked to the vessel wall. Tryptophan (Trp) is oxidized in a constitutive manner by tryptophan 2, 3-dioxygenase in liver cells, and for alternative cell types, it is catalyzed in the presence of a differently inducible indoleamine 2, 3-dioxygenase (IDO1) in the context of a specific pathophysiological environment. Resultantly, this leads to a rise in the production of kynurenine (Kyn) metabolites. Inflammation in the preliminary stages of atherosclerosis has a significant impact on IDO1, and IDO1 and the IDO1-associated pathway constitute critical mediating agents associated with the immunoinflammatory responses that characterize advanced atherosclerosis. The purpose of this review is to survey the recent literature addressing the kynurenine pathway of tryptophan degradation in CVD, and the author will direct attention to the function performed by IDO1-mediated tryptophan metabolism.